The Role of Transformative Communication in Creating a Culture of Innovation - Gularso, Kurnadi; Subekti, Imam (International Journal Labs, 2023)
Background: An organization's survival, growth, and competitive advantage depend on its agility or ability to respond quickly and effectively to changes in its internal and external environment. Creating various innovations, including implementing new systems, strategies, and programs, requires creativity to run effectively. An organizational culture that is accommodative to the changes that occur is needed to make this happen. Many studies on communication and its relationship to organizational culture suggest a reciprocal influence between the two. However, the role of transformative communication carried out by leaders in creating an organizational innovation culture has not been widely studied. A research model was developed to explain the relationship between constructs based on an analysis of the employees of a public company in Indonesia. Aim: This study emphasizes the role of transformative communication as a mediator of transformational leadership in achieving organizational innovation culture in the company implementing a new system. Method: Analysis using structural equation modeling with partial least squares estimation was applied. This research contributes to the application of transformative communication more specifically. Findings: The study's findings indicate that transformative communication plays a significant role in mediating the effects of transformational leadership on the development of an organizational innovation culture. This study concludes with some suggestions for potential future research.